From Cape Town to Kabul : rethinking strategies for pursuing women's human rights - Andrews, Penelope (Ashgate, 2012)
Using her experience of living under apartheid and witnessing its downfall and the subsequent creation of new governments in South Africa, the author examines and compares gender inequality in societies undergoing political and economic transformation. Broad in its thematic approach, the book generates challenging and complex questions about the achievement of gender equality. It will be of interest to academics interested in gender and human rights, international and comparative law.